Computational molecular structure analysis, electronic properties of sudan dye doped thioureabarium chloride crystals for nlo Applications - Subramanian Nithiyanantham; S Panimalar; P Kumaresan; K Sambath Kumar (Institute of Computer Science (IOCS), 2022)
Pure thiourea barium chloride (TBC) crystals were grown by slow evaporation from aqueous solution and slow cooling (0.1oC/ day). The growth was carried out for 21 days by keeping the bath at a temperature of 39oC. Optimal molecular structures are explored by DFT / B3LYP method with 6-31G (d, p) based synthesis. Hyper conjugative interactions, charge delocalization and intra molecular hydrogen bonding have been analyzed using natural bond orbital (NBO) analysis. Moreover lower in the HOMO and LUMO energy gap explains the eventual charge transfer interactions taking place within the molecule, which influences the biological activity of the compound and also energy serves as a measure of the excitability of a compound, the smaller the energy gap, the more easily the compound will be excited. Electronic structures were discussed and the displacement of the electron density was determined. Second – order perturbation theory analysis of the intra molecular bonds of Methyl Orange doped TBC were derived.